Informative Inter Simple Sequence Repeat (ISSR) primers for genetic analysis of coconut (Cocos nucifera L.) germplasm - R. Manimekalai (CORD, 2005)
Inter Simple Sequence Repeat (ISSR) markers are versatile and used in a number of applications viz. genetic diversity estimation, phylogenetic relationship and gene tagging in different crops. In coconut, the ISSR markers are being reported here for the first time. In the present paper, thirty-five  primers targeting to amplify the inter microsatellite  regions were screened  using  thirty  different  coconut  germplasm  accessions.  The  ISSR  primers  were evaluated based on polymorphism information content and marker index.  Out of 35 primers screened,  19 primers  produced  clear amplification  pattern.  The polymorphism  information content varied between 0.019 and 0.386, whereas, the marker index ranged from 0.019 to 5.673  among  the  primers.    Based  on  the  high  marker  index,  five  and  ten  primers  were selected.  The similarity  matrices  were constructed  separately  for five, ten and 19 primers using NYSYS software and the correlation was tested using Mantel’s test. There was high correlation  between five and ten primers with 19 primers. Hence, the primers with higher marker index (5 and 10 primers) were regarded as informative  primers. These informative primers can be used to develop more polymorphic markers in coconut for rapid screening of germplasm materials.